Design and Implementation of Network Routing by Genetic Approach in WDM Networks (International Journal of Current Engineering and Technology, 2014)
According to a fast growth of bandwidth capacity of WDM network, traffic loss due to a failure of the network components is becoming unacceptable. To overcome this difficulty, a safety method that prepares backup light-paths for each working path is now considered to improve the reliability of networks. So, this thesis proposes a network routing using genetic approach in wavelength-division-multiplexed passive optical network (WDM-PON) subject to requirements of fairness, efficiency, and cost. It proposes a network design problem for the traffic grooming and routing in WDM networks. A dynamic subcarrier assignment algorithm that respects quality of service by offering reduced average delay is proposed. Moreover, effective ways to improve its performance and reduce its complexity are provided. In this work, it is concentrated on the effects of bandwidth, delay and bit rate. This work deliberates the development in blocking probably for incoming requests while performing routing by proposed algorithm and shortest path algorithm.
Keywords: Efficient Routing, Routing in Networks, shortest path, Blocking Probability.